US Spacesuits - Thomas, Kenneth S.; McMann, Harold J. (Space Exploration, 2006)
Ken Thomas and Joe McMann have produced a magni?cent treatise on spacesuits, spacewalking, life support systems and escape systems. US Spacesuits is historical, massively comprehensive, precise, informative, relevant and readable. As an astronaut I spent 30 years in their world and in their suits. My life was in their hands. I trained on the Apollo and Skylab systems; I assisted in the devel- ment of the Skylab extravehicular activity (EVA) procedures and was a capsule communicator (capcom) on six of the Skylab walks. I helped them in the devel- ment and testing of the shuttle suits, escape systems and all the spacewalking equipment. Together with Don Peterson, I was the ?rst astronaut to test the material in space and I was the lead walker in the initial repair of the Hubble Space Telescope. In this book I am able to relive a lot of my 30 years in that world and gain new insights and perspectives on those experiences. This book is an accurate and detailed history. It is a comprehensive chronology but it is also much more. It not only tells and shows what happened but it deals with how and why things happened. It addresses the hardware and processes that came into fruition and, very importantly, also addresses the options that might have occurred, but did not. It deals with history as an evolutionary process and shows the selection and development system at work.